DISEMINASI TEKNOLOGI PEMBUATAN PUPUK ORGANIK CAIR DI NAGARI TANJUNG SANI KECAMATAN TANJUNG RAYA KABUPATEN AGAM - Efrizal Efrizal; Zozy Aneloi Noli; Ferry Lismanto Syaiful; Prima Fauziah Haq; Aulia Suci Desila; Fera Malta; Miftah Mussaumi Adi (LPPM Universitas Andalas, 2023)
The use of organic fertilizers can be a solution to reducing the application of inorganic fertilizers because they can improve the soil's physical, chemical, and biological properties to increase the quality and quantity of crop yields. One organic fertilizer that can improve soil nutrients and increase the quality and quantity of the harvest is rice-washing water waste. This waste is helpful for plants, easily obtained by farmers, and environmentally friendly; it has a low price so that farmers can afford it. The objectives of this activity are 1. to increase public knowledge and understanding of the manufacture of Liquid Organic Fertilizer (POC) derived from rice washing water waste, 2. to reduce the use of chemical fertilizers which are diverted to organic fertilizers to maintain soil and environmental quality. This activity was carried out from July to September 2022 at the Wali Jorong Sigiran Nagari Tanjung Sani Office, Tanjung Raya District, Agam Regency. The activity methods used are counseling methods and demonstration of liquid organic fertilizer (POC) making. The activity results show that partners are very interested and enthusiastic about participating in the implementation of activities in receiving the science and technology of fertilizers provided. Furthermore, the motivation of the PKK partner women community group to carry out intensive cultivation or maintenance of local plants is very large. Even the high desire of the community/partners to master the technology for making liquid organic fertilizer (POC) is given. From this activity, it can be concluded that it can increase the community's knowledge and skills in producing alternative organic fertilizers so that plant cultivation activities can run well in Nagari Tanjung Sani, Tanjung Raya District, Agam Regency, West Sumatra.